Filantropi Islam Untuk Pendidikan: Strategi Pendanaan Dompet Dhuafa dalam Program Sekolah Guru Indonesia (SGI) - Shofa, Rizka Amalia; Machali, Imam (Madania: Jurnal Kajian Keislaman, 2017)
Islamic Philanthropy for Education: Dompet Dhuafa Funding Strategy in Indonesian Teacher School Program (SGI). This study is aimed at finding out the implementation of the use of zakah funds for the Indonesian Teachers School (SGI) program, and to motivate Islamic educational institutions to empower zakah as the Islamic education funding strategy in Indonesia. This research is a qualitative research and conducted in Indonesian Teachers School office with sevent respondents using snow ball sampling technique. The methods of data collection use observation, interviews, and documentation. Data validity test used is source triangulation technique, and data analysis technique used is interactive model from Huberman and Miles. The results show that Indonesian Teachers School is a teacher delivery program in disadvantaged areas by using productive zakah funds from Dompet Dhuafa. The teacher is included in the category ashnâf fî sabilillâh so it is entitled to receive the benefit of zakah. The process of funding using zakat begins with the preparation of the Annual Budget Work Plan (RKAT), the disbursement of zakah funds, the use of zakah funds by beneficiaries (teachers), the preparation of monthly financial and activity reports by beneficiaries to the Indonesian Teachers School.